(untitled) (Research, Society and Development, 2021)
Zooplankton is a group of organisms that can help to understand the quality of aquatic ecosystems, as they are responsible for transforming energy matter, thus making it available to other links, making them important in aquatic trophodynamics. This study analyzed spatial and temporal variations in zooplankton communities found in two tidal control structures on Ilha do Maranhão, northeastern Brazil. Sampling took place from September 2017 to July 2018. Abiotic parameters (temperature, salinity, and transparency) and plankton samples were recorded monthly throughout the study period at each sampling site. The results found for the abiotic parameters showed a well-defined pattern, with a clear division between the dry and rainy periods. Forty taxa represented the zooplankton community of the São Luís tidal control structure, and from São José de Ribamar by 21 taxa, represented mainly by copepods, ichthyoplankton, foraminifera, polychaetes, and mollusks. The analysis of ecological indices of richness, evenness, and diversity showed a difference in the distribution of organisms among the study areas. We identified an important influence of the physicochemical parameters on the zooplankton communities of São Luís and São José de Ribamar, according to the statistical analyzes used in this study.